CESSION AND LEGAL EFFECTS ON THE DEBTOR'S SECURITY OBJECTS IN SETTLEMENT BAD CREDIT (Case study of Pekanbaru District Court Decision No. 129/Pdt.G/2016/PN.Pbr) - Hamler, Hamler; pasaribu, Yusuf hanafi; Darodjat, Tubagus Achmad; Akkapin, Supaphorn; Asmah, Nur (Yayasan Pusat Cendekiawan Intelektual Nusantara, 2025)
One way to resolve bad credit is carried out by banks by buying and selling receivables and transferring rights to them (cession). Based on District Court decision No.129/Pdt.G/2016/PN.Pbr, this is by means of a lawsuit by assignees who had purchased receivables from PT Bank Tabungan Negara (Persero) Tbk which had bad credit. Redirection receivables stated in 2 (two) Notarial Deeds, namely the Receivables Sale and Purchase Agreement and Transfer cessie. In announcing the verdict stated that the Pekanbaru District Court permitted the transfer of the Land Ownership Certificate which was used as collateral for the debtor above no assignees). The problem formulation is: 1. Can the sale and purchase of receivables and the transfer of rights to receivables (cessie) provide legal certainty for cessie buyers? 2. What are the legal consequences for the debtor's guarantee based on the decision of the Pekanbaru District Court Number 129/Pdt.G/2016/PN.Pbr? And study This aims to know and understand and provide answers to the problem formulation the. The type of research in this research is included in normative (doctrinal) legal research, namely research on legal aspects, legal principles, studying law which is conceptualized as norms or rules that apply in society and analyzing legal rules contained in legislation and also contained in unwritten legal norms that live and develop in society and the type of data used is secondary data sourced from materials law primer, material law secondary and materials law tertiary. From study This can be concluded that buying and selling receivables and transfer cession does not result in the end of the credit agreement made assignor with emergence This is a transfer and delivery of receivables from assignor to assignees and transfer of collateral emergence must be based on a decision through a lawsuit at the local District Court. And in this case there is no buying and selling of receivables and transfers cession is legal and does not violate the provisions of the legal terms of the agreement, in the consideration of the panel of judges that the collateral is owned emergence If the right of liability is not installed, then the item is guaranteed emergence can be used as debt repayment by changing the name to assignees, This also does not violate property stipulation what is meant by Article 1154 of the Civil Code.